Lithuanian Art - Women Experience. - Kuiziniene, Ieva; NMWA (National Museum of Women in the Arts) Washington (Vilnius : Contemporary Art Centre, 1998)
Katkeviciené, Stefanija ; Ceicyté, Juzefa ; Zilyté, Biruté ; Skliutauskaité, Adasa ; Kazé ; Rozanskaité, Teresé ; Kriauciunaité, Elvyra Katalina ; Guobiené, Irena Dauksaité ; Katiliuté, Buta ; Kasciunaité, Dalia ; Stauskaite, Jurate ; Drazdauskaité, Laima ; Jonkaityté, Danuté ; Stancikaite, Birute ; Jarosevaité, Ksenija ; Petrasiunaité, Audroné ; Bubelyté, Violeta ; Saukiené, Nomeda ; Ramunaite, Aiste ; Velaniskyté, Eglé ; Andziulyté, Ausra ; Gruodyté, Karla ; Pulyté, Eglé ; Bakauskaité, Eglé ; Urboniene, Nomeda ; Vertelkaite, Egle ; Jurksaityté, Patricija ; Morkunaité, Oruné ; Barilaité, Jurga ; Kirvelyté, Aisté ; Urbaitis, Elena ; Lukas, Giedré ; Sivickaité-Mockiené, Nijolé ; Strasevicius, Mary
biografie
Lithuanian Art - Women Experience, NMWA (National Museum of Women in the Arts) Washington, October 1998
Engels
kunstcatalogus
Keywords: Litouwen